2023
DOI: 10.1029/2023tc007881
|View full text |Cite
|
Sign up to set email alerts
|

New Constraints on the Late Oligocene‐Miocene Thermo‐Tectonic Evolution of the Southeastern Tibetan Plateau From Low‐Temperature Thermochronology

Abstract: The southeastern (SE) Tibetan Plateau (Yunnan) is characterized by low‐relief uplands that were deeply incised by large rivers. The thermal history of basement rocks in this region remains poorly investigated, while this data is needed to elucidate the complex relationship between tectonics and climate in shaping the surface. To better understand its thermo‐tectonic evolution, we carried out apatite fission track thermochronology on 31 samples collected from a large area that covers different tectonic units, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 182 publications
0
4
0
Order By: Relevance
“…Approximately 80 km northwest of the Great Bend (Figure 1 In fact, this Middle-Late Miocene rapid cooling has been widely identified from rocks obtained from most of the major river valleys of southeastern Tibet: from Early Miocene until at least ca. 11 Ma in the Salween River valley [12,39,55], starting during the Middle-Late Miocene in the Mekong River valley [41,48,56], 11-8 Ma for the Yangtze River valley (this study), 14-10 Ma in the Red River valley [15,49], 13-9 Ma in the Dadu River valley [9,57], and starting at ca. 20-14 Ma in the Yalong River valley [57,58].…”
Section: Rapid Incision Of the Tiger Leaping Gorge During The Miocenementioning
confidence: 54%
See 3 more Smart Citations
“…Approximately 80 km northwest of the Great Bend (Figure 1 In fact, this Middle-Late Miocene rapid cooling has been widely identified from rocks obtained from most of the major river valleys of southeastern Tibet: from Early Miocene until at least ca. 11 Ma in the Salween River valley [12,39,55], starting during the Middle-Late Miocene in the Mekong River valley [41,48,56], 11-8 Ma for the Yangtze River valley (this study), 14-10 Ma in the Red River valley [15,49], 13-9 Ma in the Dadu River valley [9,57], and starting at ca. 20-14 Ma in the Yalong River valley [57,58].…”
Section: Rapid Incision Of the Tiger Leaping Gorge During The Miocenementioning
confidence: 54%
“…The emplacements of these plutons are regarded as indicative of lithospheric delamination or continental subduction during the Eocene [27]. Therefore, recent studies of the Jianchuan Basin have suggested that fluvial incision associated with the generation of topographic relief in SETP occurred during the late Eocene-Early Miocene [5,[10][11][12], implying that the formation of the Great Bend and regional drainage rearrangement took place during the same period.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the Cenozoic, along with the collision of the Indian and Eurasian plates, and resulting compression, the highest in the world has been formed-Tibetan Plateau (Molnar and Tapponnier 1975;England 1997;Chen et al 2017;He et al 2023;Ma et al 2023a, b). The Tibetan Plateau has a profound impact on atmospheric circulation and thus global climate, and is an ideal place for scientific research (Tapponnier 2001).…”
Section: Introductionmentioning
confidence: 99%